Pancreatic Rupture in Mid-Pregnancy Mimicking Obstetric Emergency - Ahmad Bukhoeri; Putri Sekar Wiyati; Lubena Lubena; Ahmad Fathi Fuadi (Journal of Social Research, 2026)
Suspicion for non?obstetric intra?abdominal injuries in pregnant patients is often overlooked due to the striking clinical similarity to more common obstetric causes such as placental abruption or uterine rupture. This report discusses diagnostic pitfalls in a fatal pancreatic rupture case masquerading as a catastrophic obstetric event. This case highlights the "obstetric bias" in acute shock management. The Couvelaire uterus and atonia were secondary consequences of systemic hypoperfusion rather than the primary source of hemorrhage. A 25-year-old woman at 24 weeks gestation presented with profound hemorrhagic shock (BP 42/26 mmHg, GCS 3), a rigid "wooden" uterus, and intrauterine fetal demise. While initial findings suggested concealed placental abruption, laparotomy revealed a Couvelaire, atonic uterus without rupture. Further systematic exploration discovered a high-grade pancreatic tail rupture with a 7,000 mL retroperitoneal hemorrhage. Despite a total hysterectomy and damage-control measures, the patient succumbed to refractory shock and multi-organ dysfunction postoperatively. Clinicians must remain aware of non-obstetric cause of hemodynamic collapse in atypical presentations to prevent diagnostic delay. Prompt adoption of trauma?style algorithms, damage?control surgery, and massive transfusion protocols are vital when surgical findings do not correlate with the degree of hemorrhage.